Robust Voltage Regulation of a Stand Alone Uncertain Single-Stage Boost Inverter - Rojas-Lobos, F; Verdugo-Naranjo, D; Borquez-Berenguer, J; Acosta-Barbosa, K (Institute of Electrical and Electronics Engineers Inc., 2018)
This paper focuses on the robust control of a single stage boost inverter using a model that accounts for both small and big signal properties of the inverter. The aim is to determine a state feedback controller for the small signal model such that it is able to reject perturbations existing on the three-phase currents while keeping the system stable and with a response quick enough. Based on the well-known theory of robust control, a feedback controller is proposed in order to minimize the H∞ norm of the system while taking in account the variable load and a D-Stability region that will guarantee the speed required for the perturbation effect to decay. The proposed controller is simulated and the results are analyzed and discussed. © 2018 IEEE.